Effect of Border Markets on the Economy of West Azerbaijan Province, Iran - Sayyed Hessam-aldin HEDAYATZADEH; Ramin Bashir KHODAPARASTI (Revista de Management Comparat International)
The present study attempts to assess the performance of border markets and their effects on the sustainable development of border regions of Iran. Tamarchin, the oldest border market of Piranshahr, West Azerbaijan Province, Iran, was selected as the case for the study since it has ranked first in the country, both quantitatively and qualitatively. The data for the study was collected from two different sources: official statistics released by the Customs Office, the Ministries of Commerce and Corporation of Iran during 2001-2007 and data gathered from a questionnaire distributed among some active West Azerbaijan border traders and also from a face-to-face interview with those traders. The results of the study indicated that considering high growth potential and many other advantages of the province, West Azerbaijan can play a significant role in the creation and establishment of border markets of the country.